Overview of pregnant women’s satisfaction with antenatal care services using the customer satisfaction index (CSI) - I Nengah Prama Baswara Andakara Yasa; Putu Arya Suryanditha; Luh Gede Pradnyawati (Science Midwifery, 2026)
Background: The Maternal Mortality Ratio (MMR) in Indonesia remains high at 189 per 100,000 live births in 2020. One contributing factor to this condition is low compliance among pregnant women in attending antenatal care (ANC) visits, which is presumed to be influenced by their level of satisfaction with antenatal services. This study aimed to describe and analyze pregnant women’s satisfaction with the quality of antenatal care services at BaliMed Karangasem Hospital. This study employed a descriptive analytic design using the SERVPERF questionnaire, which evaluates five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using the Customer Satisfaction Index (CSI). The results showed that all service quality dimensions had high levels of satisfaction and importance. The highest satisfaction score was observed in the responsiveness dimension (4.57), while the lowest was in tangibles (4.48). The highest importance score was found in the assurance dimension (4.68), whereas the lowest importance score was in tangibles (4.52). The CSI value of 90.5% indicated a “very satisfied” category.